Antagonistic activity of three Aspergillus isolates against Fusarium wilt of banana - Iman Hidayat; Lita Citra Dewi; Dalia Sukmawati (Journal of Microbial Systematics and Biotechnology, 2019)
Endophytic fungi have been known to play a role in protecting their host plants against diseases and extreme environments. The purpose of this study was to determine the antagonistic activity of three Aspergillus isolates against F. oxysporum f. sp. cubense (Foc), and to identify the Aspergillus identity using multilocus phylogeny analysis. Antagonistic assay by dual culture method showed that the Aspergillus sp. strain PD2, strain PD4, and strain PD5 inhibited the growth of Foc isolate by 37.31%, 26.52%, and 12.04%, respectively. Multilocus phylogeny based on ITS rDNA, beta-tubulin, and calmodulin genes sequences showed that the Aspergillus strain PD2 and strain PD4 belong to A. section Terrei, while the Aspergillus sp. strain PD5 was identified as A. sydowii of the A. sect. Versicolores.